Sufficient To Have Stood: The Lady Unparalyzed in Milton’s A Maske Presented at Ludlow Castle - Goldfarb Styrt, Philip (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2025)
One of the central figures of John Milton’s A Maske Presented at Ludlow Castle is that of the protagonist, the Lady, paralyzed in a chair arguing with the villain Comus. This article argues that while the Lady does argue with Comus from the chair, she is not necessarily paralyzed, and that her potential ability to move creates space for productions to emphasize her virtue, her agency, and the difference between her experience of the masque and that of her brothers. These possibilities connect the masque to early modern masquing and broader theatrical traditions that emphasized female agency and voice.